Prosthetic management of a hemimandibulectomy patient using tilted implant protocol with 3-year follow-up - Nag, P. Venkat Ratna (J Indian Prosthodont Soc, 2020)
Surgical resection of the mandible due to the presence of benign or malignant tumor commonly results in the deviation of the remaining mandible toward the defective side. Based on the location and extent (mandible), various surgical approaches such as marginal, segmental, and hemi or subtotal or total mandibulectomy can be executed. The restoration of normal form, function, and esthetic is often challenging in the prosthetic rehabilitation of patients with hemimandibulectomy. A 36-year-old male patient reported with a chief complaint of difficulty in eating and speech. Past dental history of the patient revealed ameloblastoma of the left mandibular alveolus, which was surgically operated 6 years back with a wide resection of the tumor with left-sided hemimandibulectomy without disarticulation and reconstruction with an osteocutaneous free fibula flap (from the right leg) fixed with a screw plate system. This case report suggests that the rehabilitation of surgically resected patients using tilted implant technique can reach a desirable prosthetic outcome. This clinical report describes prosthetic management (implant-supported fixed prosthesis) of a hemimandibulectomy patient using tilted implants and screw-retained prosthetic solutions using multiunit abutments. It improves speech, masticatory efficiency, and esthetics without any further deviation of the mandible with a 3-year follow-up.